MENINGKATKAN HASIL BELAJAR TARI MELALUI PENERAPAN METODE THINK–PAIR–SHARE DI SMK NEGERI 2 PADANG - Yuni, Rice Mai; Yuliasma, Yuliasma; Iriani, Zora (FBS Universitas Negeri Padang, 2019)
AbstractThis article aims to improve the learning outcomes of the art of dance at SMK Negeri 2 Padang in learning the art of dance.This type of research is the research action class (PTK) using the Think-Pair-Share. Research procedure consists of 4 stages namely action planning, implementation, observation, reflection and reflection. The implementation of the actions conducted as many as two cycles. data collection Techniques used are observation, tests of the subject, as well as documentation. Data analysis technique used is the formula ketuntasan klasial. The results of this study showed that the increase in the acquisition value of the students. It can be seen rising average value of students from pratindakan 71.56 then Cycle I and cycle II 74, 2. Learning outcomes students class X Accounting I SMK N 2 Padang in learning the art of dance with the application of the method of the Think-Pair-Share on Twelve Serampang dance learning increases. The results looked when students have been active in the classroom so that learning becomes effective and efficient as well as impact to the improvement of student learning outcomes. Then, in the application of method of the Think-Pair-Share students more courageous in expressing opinions enhances socialization sertakomunikasi between students.Keywords: Learning Outcomes, Learning The Art Of Dance, Think-Pair-Share